2014
DOI: 10.1194/jlr.m043299
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress impairs cholesterol efflux and synthesis in hepatic cells

Abstract: Metabolic disorders such as type 2 diabetes cause hepatic endoplasmic reticulum (ER) stress, which affects neutral lipid metabolism. However, the role of ER stress in cholesterol metabolism is incompletely understood. Here, we show that induction of acute ER stress in human hepatic HepG2 cells reduced ABCA1 expression and caused ABCA1 redistribution to tubular perinuclear compartments. Consequently, cholesterol efflux to apoA-I, a key step in nascent HDL formation, was diminished by 80%. Besides ABCA1, endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 65 publications
1
50
0
Order By: Relevance
“…6, C-E). Others have reported that TM blocks de novo cholesterol synthesis via direct inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (59) and reduces cholesterol efflux (60). However, a model FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…6, C-E). Others have reported that TM blocks de novo cholesterol synthesis via direct inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (59) and reduces cholesterol efflux (60). However, a model FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol efflux was measured as described previously [31]. Briefly, HepG2 cells were cultured in DMEM media containing 15% FBS, trace labeled with 1 µCi/ml 3 H-cholesterol (Perkin-Elmer, USA) overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Excess unesterified cellular cholesterol is known to induce ER stress in a number of cell types, including hepatocytes [4850]. Conversely, ER stress reduces ABCA1 and SR-BI and impairs cholesterol efflux in cultured hepatocytes [51]. Similar to G5G8, AdGRP78 increased ABCA1 and SR-BI in db/db mice, suggesting that ER dysfunction perturbs multiple facets of hepatic sterol metabolism in db/db mice.…”
Section: Discussionmentioning
confidence: 99%